COVID-19 catalysing assessment transformation: A case of the online open book examination - Meeran, S.; Davids, M. N. (South African Journal of Higher Education, 2021)
Under COVID-19 lockdown conditions, the imposition of social distancing and restricted mobility, disrupted the traditional way of assessment in higher education. The closed book examination, conducted under proctored conditions, had to be substituted for the online open book examination (OOBE), posing challenges to both conventional and Open Distance Learning (ODL) institutions. The OOBE became a new experience to lecturers and students. Considering COVID-19 as a potential catalyst for educational transformation, the experiences gained in this format of assessment presents a valuable frame of reference for future learning. The aim is to extract lessons from this innovative learning experience to inform future assessment practices. The study is set in the context of a B.Ed. (Hons) compulsory module, offered at an Open Distance Learning (ODL) institution in South Africa. It is guided by the research question: “what were students’ experiences of their first online, open-book final examination and what are the implications for policy, practice and research?” This is a qualitative study, using as data, student emails on their experiences of the OOBE. The results show that the OOBE is an innovative assessment practice in higher education, in need of deeper understanding and (re)training. We conclude that the OOBE offers transformational opportunities in higher education assessment practices, to replace the traditional closed-book examination. We make recommendations to assist lecturers and students in approaching the OOBE in future.